Relative contribution of iron burden, HFE mutations, and insulin resistance to fibrosis in nonalcoholic fatty liver - Bugianesi, Elisabetta; Manzini, Paola; D'Antico, Sergio; Vanni, Ester; Longo, Filomena; Leone, Nicola; Massarenti, Paola; Piga, Antonio; Marchesini, Giulio; Rizzetto, Mario (Hepatology (Baltimore, Md.), 2004)
The mechanism(s) determining the progression from fatty liver to steatohepatitis is currently unknown. Our goal was to define the relative impact of iron overload, genetic mutations of HFE, and insulin resistance on the severity of liver fibrosis in a population of subjects with nonalcoholic fatty liver disease (NAFLD) who had low prevalence of obesity and no overt symptoms of diabetes. In a cohort of 263 prospectively enrolled patients with NAFLD, 7.4% of patients had signs of peripheral iron overload and 9% had signs of hepatic iron overload, but 21.1% had hyperferritinemia. The prevalence of C282Y and H63D HFE mutations was similar to the general population and mutations were not associated with iron overload. Although subjects were on average only moderately overweight, insulin sensitivity, measured both in the fasting state and in response to oral glucose, was lower. Univariate analysis demonstrated that the presence of severe fibrosis was independently associated with older age, female sex, overweight, aspartate/alanine aminotransferase ratio, serum ferritin level, fasting glucose and insulin levels, decreased insulin sensitivity, and with histologic features (degree of necroinflammation and steatosis). After adjustment for body mass index (BMI), age, sex, and degree of steatosis, ferritin levels (odds ratio [OR] = 1.77; 95% CI = 1.21‐ 2.58; P = .0032) and the oral glucose insulin sensitivity (OR = 0.53; CI = 0.33‐0.87; P = .0113) were independent predictors of severe fibrosis. In conclusion, the current study indicates that insulin resistance is a major, independent risk factor for advanced fibrosis in patients with NAFLD. Increased ferritin levels are markers of severe histologic damage, but not of iron overload. Iron burden and HFE mutations do not contribute significantly to hepatic fibrosis in the majority of patients with NAFLD. (HEPATOLOGY 2004;39:179–187.)